Strength demands for elite basketball shooting performance Dominic Olufunnilola Leah / Talabi Adetayo Ebun, Niyi- Odumosa F. A - Ebun, Talabi Adetayo; F. A, Niyi- Odumosa (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2016)
The purpose of this study was to identify the strength demands of the lay-up, free throw and jump shots. General strength has been established as significant to general fitness of the athletes in order to maintain stability, protect the body from injuries and delay the onset of fatigue especially in repeated movements as found in the game of basketball. The specific strength is paramount and is a strength type of training harmonized with specific skill for optimal performance. Correlation research design was used while purposive sampling technique was used to select the sample. The eighteen registered players of the Niger potters’ team of Nigeria were used as the participants. Descriptive statistics of mean and standard deviation were used describe the data while Pearson Product Moment correlation Coefficient (r) was used to test significant relationship. The findings revealed that only the general leg explosive power training was needed for the three styles of shooting (r= 0.07,0.03 &,-0.06<.05) while general strength fitness of the abdominal muscles are required for the lay-up and jump shot (r= 0.33 &-0.23<.05). However, specific abdominal strength has significant relationship with the free throw shooting ability (r=0.517>0.05), while specific arm strength was significantly related with the jump shot ability (’r=-0.57>0.05). These results indicated that specific athletic strength harmonized with the technique demanded by the arms for jump shot, and the abdominal muscles for free throw shot is paramount to optimal performance in these shooting styles.